Calf-raise senior: a new test for assessment of plantar flexor muscle strength in older adults: protocol, validity, and reliability - André HI (Dove Medical Press, 2016)
Helô-Isa André,1 Filomena Carnide,1 Edgar Borja,2 Fátima Ramalho,1,2 Rita Santos-Rocha,1,2 António P Veloso1 1Laboratory of Biomechanics and Functional Morphology, Interdisciplinary Study Centre for Human Performance (CIPER), Faculty of Human Kinetics (FMH), University of Lisbon, Portugal; 2Sports Science School of Rio Maior (ESDRM), Polytechnic Institute of Santarém, Portugal Purpose: This study aimed to develop a new field test protocol with a standardized measurement of strength and power in plantar flexor muscles targeted to functionally independent older adults, the calf-raise senior (CRS) test, and also evaluate its reliability and validity.Patients and methods: Forty-one subjects aged 65 years and older of both sexes participated in five different cross-sectional studies: 1) pilot (n=12); 2) inter- and intrarater agreement (n=12); 3) construct (n=41); 4) criterion validity (n=33); and 5) test–retest reliability (n=41). Different motion parameters were compared in order to define a specifically designed protocol for seniors. Two raters evaluated each participant twice, and the results of the same individual were compared between raters and participants to assess the interrater and intrarater agreement. The validity and reliability studies involved three testing sessions that lasted 2 weeks, including a battery of functional fitness tests, CRS test in two occasions, accelerometry, and strength assessments in an isokinetic dynamometer.Results: The CRS test presented an excellent test–retest reliability (intraclass correlation coefficient [ICC] =0.90, standard error of measurement =2.0) and interrater reliability (ICC =0.93–0.96), as well as a good intrarater agreement (ICC =0.79–0.84). Participants with better results in the CRS test were younger and presented higher levels of physical activity and functional fitness. A significant association between test results and all strength parameters (isometric, r=0.87, r2=0.75; isokinetic, r=0.86, r2=0.74; and rate of force development, r=0.77, r2=0.59) was shown.Conclusion: This study was successful in demonstrating that the CRS test can meet the scientific criteria of validity and reliability. The test can be a good indicator of ankle strength in older adults and proved to discriminate significantly between individuals with improved functionality and levels of physical activity. Keywords: elderly, heel-raise test, ankle, isometric, strength, functionality